Closing markets to biotechnology: does it pose an economic risk if markets are globalised?. (2nd January 2007) - Smyth, Stuart; Kerr, William A.; Davey, Kelly A.
This paper compares international trading patterns for canola, corn and soybean varieties prior to commercialisation of the Genetically Modified (GM) varieties with present trading patterns that include GM varieties. Any marketplace changes that have occurred are analysed to determine the cause for any market shifts. GM canola, corn and soybeans entered the marketplace successfully, but some international markets were lost because of the commercialisation of the GM varieties. The paper examines if these industries were able to successfully identify any new marketplace opportunities and shift commodity exports into new markets.